Mineração de dados para entender os fatores de influência da qualidade educacional do Maranhão - SOARES, Raimundo de Castro (2022)
The state of Maranhão has low levels of quality in basic education, as can be seen through national performance assessments over the years. The problem of low educational quality can be approached and investigated from the viewpoint of several areas. One of them is the use of educational data mining, which is increasingly present in scientific studies, and is also used to support decision-making by public policy makers. However, research with data from an area or a particular location may still be scarce, as is the case in the state of Maranhão. This master’s research aims to understand what are the factors that influence the quality of public education in the state of Maranhão. For this purpose, data mining techniques were used, such as exploratory data analysis, correlation analysis, factor analysis, regression and decision tree. The data used are from public high schools in Maranhão. The results of this study show a diagnosis of the state’s educational situation, with factors that significantly influence and others that are not so important in the performance of education.